2017
DOI: 10.7567/jjap.56.078002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing based on multimodal interference in polymer optical fibers: Room-temperature sensitivity enhancement by annealing

Abstract: To date, we have developed a temperature sensor based on multimodal interference in a polymer optical fiber (POF) with an extremely high sensitivity. Here, we experimentally evaluate the influence of annealing (heat treatment) of the POF on the temperature sensitivity at room temperature. We show that the temperature sensitivity is enhanced with increasing annealing temperature, and that, by annealing the POF at 90°C, we can achieve a temperature sensitivity of +2.17 nm/°C, which is 2.9 times larger than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In addition to these achievements, we have found that the strain and temperature sensitivities do not largely depend on the length of the MMF [25], that the temperature sensitivity at room temperature can be enhanced by annealing [33] and that the modal interference in partially chlorinated GI POFs is potentially applicable to high-sensitivity temperature measurement with low strain sensitivity [34]. Future tasks include clarification of the critical wavelength dependence on fiber properties [15] (which will be a useful guideline for the researchers who search for new materials with high sensitivities), extremely large strain sensing with plastic deformation [35], clarification of the shortest length of the MMF, clarification of cross effect of strain and temperature [36], and discriminative (not distributed) sensing of strain, temperature, and some other parameters by combined use of FBG and/or Brillouin scattering.…”
Section: Resultsmentioning
confidence: 81%
“…In addition to these achievements, we have found that the strain and temperature sensitivities do not largely depend on the length of the MMF [25], that the temperature sensitivity at room temperature can be enhanced by annealing [33] and that the modal interference in partially chlorinated GI POFs is potentially applicable to high-sensitivity temperature measurement with low strain sensitivity [34]. Future tasks include clarification of the critical wavelength dependence on fiber properties [15] (which will be a useful guideline for the researchers who search for new materials with high sensitivities), extremely large strain sensing with plastic deformation [35], clarification of the shortest length of the MMF, clarification of cross effect of strain and temperature [36], and discriminative (not distributed) sensing of strain, temperature, and some other parameters by combined use of FBG and/or Brillouin scattering.…”
Section: Resultsmentioning
confidence: 81%
“…If a higher sensitivity is preferable, the dip nearest to C should be used; while if a wider strain/temperature dynamic range is preferable, it may not be the best dip to be selected. To date, when the MMF is a PFGI-POF, a dip around 1350 nm has been often used for its higher sensitivity [16,19,20].…”
Section: Principlementioning
confidence: 99%
“…Sensing technology of strain and temperature using optical fibers has been an active area of research for many decades, and a wide variety of configurations have been developed thus far. They operate based on fiber Bragg gratings [1,2,3], long-period gratings [4,5], Brillouin scattering [6,7,8,9], Raman scattering [10,11], optical interference [12,13,14,15,16,17,18,19,20,21,22,23,24], and many others. Among numerous types of interference-based sensors, those based on intermodal interference in multimode fibers (MMFs) have recently attracted a considerable attention owing to their system simplicity and cost efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations